2018
DOI: 10.1101/276493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Improves Facial Dysmorphology Associated with Down Syndrome

Abstract: 33In Down syndrome (DS), the overall genetic imbalance caused by trisomy of chromosome 21 leads to a 34 complex pleiotropic phenotype that involves a recognizable set of facial traits. Several studies have 35shown the potential of epigallocatechin-3-gallate (EGCG), a green tea flavanol, as a therapeutic tool for 36 alleviating different developmental alterations associated with DS, such as cognitive impairment, skull 37 dysmorphologies, and skeletal deficiencies. Here we provide for the first time experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This suggests that the effect of EGCG on bone health is dose-and/or sex-dependent, and thus could not be observed in mice as all were male. As for which is the specific mechanism for the bone remodeling, a recent study analyzing the effect of EGCG on cranial morphology in children with DS hypothesized a role of NFAT through DYRK1A, which is inhibited by EGCG [18]. Whether the changes in bone mass could be considered an adverse event is discussable and needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the effect of EGCG on bone health is dose-and/or sex-dependent, and thus could not be observed in mice as all were male. As for which is the specific mechanism for the bone remodeling, a recent study analyzing the effect of EGCG on cranial morphology in children with DS hypothesized a role of NFAT through DYRK1A, which is inhibited by EGCG [18]. Whether the changes in bone mass could be considered an adverse event is discussable and needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies, specifically in DS have shown that the effects of EGCG on bone structure depend on dosage [16], with high dosages being detrimental [17]. In humans, a single study has looked into the effect of EGCG on the skeletal system, focusing on facial morphology, with the most relevant effects on the younger subjects (between 0 and 3) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this include early diagnosis of fetal alcohol spectrum disorder [12], epilepsy [1], Down syndrome [11] or schizophrenia [6].…”
Section: Introductionmentioning
confidence: 99%